Filipino youth's concerns and worries and their ways of coping - Lapena, Ma. Angeles Guanzon; Tarroja, Maria Caridad H.; Tirazona, Maria Andrea S.; Fernando, Katrina C. (Philippine journal of psychology)
'Using a social constructivist perspectives, this qualitative research looked into selected Filipino youth's worries and concerns and how they coped with their children. This research showed that even without intervention, Filipino youth were able to cope with their difficulties by relying on their inner resources."